Neurocognitive profiles in help-seeking individuals: comparison of risk for psychosis and bipolar disorder criteria. Issue 16 (December 2014) - Metzler, S.; Dvorsky, D.; Wyss, C.; Müller, M.; Traber-Walker, N.; Walitza, S.; Theodoridou, A.; Rössler, W.; Heekeren, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Neurocognitive deficits are important aspects of the schizophrenic disorders because they have a strong impact on social and vocational outcomes. We expanded on previous research by focusing on the neurocognitive profiles of persons at high risk (HR) or ultra-high risk (UHR) for schizophrenic and affective psychoses. Our main aim was to determine whether neurocognitive measures are sufficiently sensitive to predict a group affiliation based on deficits in functional domains. Method. This study included 207 help-seeking individuals identified as HR (n = 75), UHR (n = 102) or at high risk for bipolar disorder (HRBip; n = 30), who were compared with persons comprising a matched, healthy control group (CG; n = 50). Neuropsychological variables were sorted according to their load in a factor analysis and were compared among groups. In addition, the likelihood of group membership was estimated using logistic regression analyses. Results. The performance of HR and HRBip participants was comparable, and intermediate between the controls and UHR. The domain of processing speed was most sensitive in discriminating HR and UHR [odds ratio (OR) 0.48, 95% confidence interval (CI) 0.28–0.78, p = 0.004] whereas learning and memory deficits predicted a conversion to schizophrenic psychosis (OR 0.47, 95% CI 0.25–0.87, p = 0.01). Conclusions. Performances on neurocognitive tests differed among our three at-risk groups and may therefore be useful in predicting psychosis. Overall, cognition had a profound effect on the extent of general functioning and satisfaction with life for subjects at risk of psychosis. Thus, this factor should become a treatment target in itself.